2021
DOI: 10.3389/fmicb.2021.769965
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Intestinal Bacterial Microbiomes of Euschistus heros and Piezodorus guildinii Collected in Brazil and the United States

Abstract: Background: Herbivorous insects are one of the main biological threats to crops. One such group of insects, stink bugs, do not eat large amounts of tissue when feeding on soybean, but are damaging to the quality of the seed yield as they feed on green developing seeds leading to poorly marketable harvests. In addition to causing physical damage during sucking-feeding activities, the insects can also transmit microbial pathogens, leading to even greater yield loss. Conducting surveys of the insect intestinal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…OTU 2 showed significant temporal variation, decreasing in relative abundance from 10.0 to 0.062% from 2019 to 2020 ( Supplementary Tables S8 , S9 ). Enterobacteriaceae is also highly represented in the gut microbiota of insects ( Hernández-García et al, 2017 ; Moro et al, 2021 ) and nematodes ( Zimmermann et al, 2020 ; Zhou et al, 2022 ). This suggests that Enterobacteriaceae may be residents of the tardigrade digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…OTU 2 showed significant temporal variation, decreasing in relative abundance from 10.0 to 0.062% from 2019 to 2020 ( Supplementary Tables S8 , S9 ). Enterobacteriaceae is also highly represented in the gut microbiota of insects ( Hernández-García et al, 2017 ; Moro et al, 2021 ) and nematodes ( Zimmermann et al, 2020 ; Zhou et al, 2022 ). This suggests that Enterobacteriaceae may be residents of the tardigrade digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al confirmed that the gut bacterial structure of G. molestacan be influenced by the host plant [ 32 ]. Moro et al showed that the diversity of gut microbes of the same species in regions was different [ 33 ]. Jesús M. et al confirmed that different time scales strongly influence the diversity, composition and metabolic capabilities of Brithys crini gut microbial communities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…OTU 2 showed significant temporal variation, decreasing in relative abundance from 10.0% to 0.062% from 2019 to 2020 (Table S8, Table S9). Enterobacteriaceae is also highly represented in the gut microbiota of insects (Moro et al 2021;Hernández-García et al 2017) and nematodes (Zhou et al 2022;Zimmermann et al 2020). This suggests that Enterobacteriaceae may be residents of the tardigrade digestive tract.…”
Section: Tardigrade-associated Taxamentioning
confidence: 99%